Longitudinal Improvements in Radiation Exposure in Cardiac Catheterization for Congenital Heart Disease: A Prospective Multicenter C3PO-QI Study. (May 2020) - Quinn, Brian P.; Cevallos, Priscila; Armstrong, Aimee; Balzer, David; El-said, Howaida; Foerster, Susan; Glatz, Andrew C.; Goodman, Andrea; Goldstein, Bryan; Hainstock, Michael; Janssen, Dana; Kreutzer, Jacqueline; et al.
Abstract : Background: The C3PO-QI (Congenital Cardiac Catheterization Project on Outcomes – Quality Improvement), a multicenter registry launched in 2015, instituted quality improvement (QI) initiatives to reduce patient radiation exposure. Through regular collaboration, this initiative would allow for harmony among active participants, maximizing efforts and efficiency at achieving radiation best practices. This study sought to report these efforts with a detailed methodology for which institutions can target initiatives, reducing radiation exposure, and increasing patient safety. Methods: Data were collected prospectively by 8 C3PO-QI institutions between January 1, 2015 and December 31, 2017. Radiation exposure was measured in dose area product per body weight (dose area product/kg; µGy*m 2 /kg) and reported by expected radiation exposure categories (REC) and institution for 40 published unique procedure types. Targeted interventions addressing selected strategic domains for radiation reduction were implemented in the pediatric catheterization labs of the C3PO-QI institutions. Results: The study consisted of 15 257 unique cases. Median exposure (dose area product/kg) was decreased by 30% for all procedures. Dose area product/kg was reduced in all 3 REC, with the greatest improvement observed in REC I (REC I, −37%; REC II, −23%; REC III, −27%). Although the baseline radiation exposures and exact percent decrease varied across all C3PO-QI sites, each institution demonstrated improvements in radiation dose over time. These improvements occurred with the implementation of institution-specific QI interventions accelerated by participation in the C3PO-QI multicenter collaborative. Conclusions: Substantial radiation dose reductions can be achieved using targeted QI methodology and interventions. Participation in a multicenter QI collaborative may accelerate improvement across all centers due to enhanced engagement and shared learning between sites.